Investigating the impact of terminal heat stress on contrasting wheat cultivars: a comprehensive analysis of phenological, physiological, and biochemical traits - Kumar, Hitesh; Chugh, Vishal; Kumar, Manoj; Gupta, Vikas; Prasad, Shambhoo; Kumar, Satish; Singh, Chandra Mohan; Kumar, Rahul; Singh, Bhupendra Kumar; Panwar, Gurusharan; Kumar, Mukul (Frontiers in Plant Science, 2023)
Terminal heat stress has become one of the major threat due to global climate change and significantly affecting production and productivity of wheat crop thereby making it necessary to identify the key traits and genotypes to breed heat tolerant genotypes. The present study was undertaken with the objective to compare the effects of heat stress (HSE) and extended heat stress (EHSE) on pheno-physio-biochemical traits of contrasting heat tolerant and susceptible genotypes during reproductive phase. Phenological traits exhibited significant reduction under EHSE compared to HSE. Heat tolerant genotypes maintained balanced pheno-physio-biochemical traits while heat-sensitive genotypes showed significant reduction under both stress regimes. Among phenological traits, DM (R 2 =0.52) and BY (R 2 =0.44) have showed positive effect on seed yield indicating that the biomass and crop duration contributed towards yield advantage under stress. At grain filling stage, normalized difference vegetation index (NDVI) and chlorophyll (Chl) showed consistently significant positive effect on grain yield under HSE and EHSE enhanced photosynthesis owing to delayed senescence and remobilization of assimilates under terminal heat stress. Biochemical activity of superoxide dismutase (SOD), peroxidase (POX) and ascorbate peroxidise (APX) was induced in tolerant genotypes under HSE. Correlation of canopy temperature with pheno-physio-biochemical traits remained static under HSE and EHSE suggesting CT as the best selection parameter for heat tolerance. The traits showing positive association with yield and that are less affected under stress could be used for selecting tolerant genotypes under stress environments. These tolerant genotypes can be used to develop mapping populations to decipher the genes conferring tolerance as well as to study the molecular basis of tolerance.